2015
DOI: 10.3988/jcn.2015.11.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Benign Multiple Sclerosis is Associated with Reduced Thinning of the Retinal Nerve Fiber and Ganglion Cell Layers in Non-Optic-Neuritis Eyes

Abstract: Background and PurposeIt is exceedingly difficult to differentiate benign multiple sclerosis (BMS) from relapsing-remitting multiple sclerosis (RRMS) based on clinical characteristics, neuroimaging, and cerebrospinal fluid tests. Optical coherence tomography (OCT) allows quantification of retinal structures, such as the retinal nerve fiber layer (RNFL) thickness, at the optic disc and the ganglion cell layer (GCL) at the macula, on a micrometer scale. It can also be used to trace minor alterations and the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 31 publications
(62 reference statements)
12
32
0
Order By: Relevance
“…Results from a study seem to suggest that GCIP thinning occurs earlier than RNFL thinning . We replicated previous studies that found thinning in the GCIP after optic neuritis . As well, we demonstrated, like other reports, thinning of the RNFL and GCIP on OCT even in MS eyes without a history of optic neuritis .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results from a study seem to suggest that GCIP thinning occurs earlier than RNFL thinning . We replicated previous studies that found thinning in the GCIP after optic neuritis . As well, we demonstrated, like other reports, thinning of the RNFL and GCIP on OCT even in MS eyes without a history of optic neuritis .…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies using OCT have shown that optic neuritis eyes of MS patients, and even nonoptic neuritis eyes of MS patients, exhibit thinning of retinal layers compared to healthy controls. This phenomenon has been consistently found in the peripapillary retinal nerve fiber layer (RNFL), as well as in the ganglion cell layer + inner plexiform layer (GCIP) from which retinal nerve fiber axons originate . Within the temporal quadrant of peripapillary RNFL lies the papillomacular bundle (PMB), which serves central vision.…”
Section: Introductionmentioning
confidence: 97%
“…Our data and the data from the four previously reported studies were meta‐analysed, further confirming significant differences in pRNFL and nonsignificant differences in GC‐IPL and mRNFL, indicating the robustness and reliability of our findings (Huang‐Link et al. ; Lange et al. ; Monteiro et al.…”
Section: Discussionmentioning
confidence: 97%
“…Since then, an increased interest in the application of OCT technology led to a large number of studies on the retinal changes in MS patients with and without previous ON episodes (non-ON). So far, studies using spectral-domain OCT have revealed that the retina in non-ON eyes shows thinner peripapillary RNFL (pRNFL) than healthy controls [1619]. …”
Section: Multiple Sclerosismentioning
confidence: 99%